Shut out : low income mothers and higher education in post-welfare America - Polakow, Valerie (State University of New York Press, 2004)
Annotation "Shut Out exposes in vivid detail the economic, educational, and existential struggles that poor single mothers confront in light of current Welfare-to-Work policies. According to the editors, these mandates strip women of their educational rights by denying them access to higher education, thus obstructing their aspirations to exit poverty and attain family self-sufficiency. The editors examine the requirements of the 1996 "welfare reform" bill and outline how states have varied in responses to limited post-secondary options within the framework of national legislation. The book shows how mothers and their allies have organized collectively to try to secure pro-education policies, and how individuals have resisted work, developed individual and family strategies, and triumphed in their pursuit of post-secondary education under extreme social and emotional duress. In outlining the multiple obstacles and policy restrictions that low income women face, the book also demonstrates successful programsthat afford women educational opportunities. Included are the latest in legislative updates, policy and advocacy recommendations, and possible future directions